Intraoperative graft flow profiles in coronary artery bypass surgery: A meta‐analysis. Issue 2 (15th November 2019) - Silva, Manuela; Rong, Lisa Q; Naik, Ajita; Rahouma, Mohamed; Hameed, Irbaz; Robinson, Bryce; Ruan, Yongle; Jiang, Yuan; Abed, Anas W; Girardi, Leonard N; Gaudino, Mario
Abstract: Background: Conduits used in coronary artery bypass artery grafting (CABG) have different properties and flow profiles. We compared intraoperative mean graft flow (MGF) between arterial and venous conduits, off‐pump CABG (OPCABG) and on‐pump CABG (ONCABG) procedures, skeletonized and pedicled internal mammary artery (IMA) grafts, and pulsatility index (PI) between OPCABG and ONCABG, in pairwise meta‐analyses. Methods: Following a systematic literature search, all studies comparing MGF in arterial and venous grafts, were included. The primary endpoint was comparison of pooled MGF between arterial and venous grafts. Secondary endpoints were comparisons of pooled MGF in OPCABG vs ONCABG, anastomosed skeletonized vs pedicled IMA grafts, free skeletonized vs pedicled IMA grafts and PI in OPCABG versus ONCABG. Results: A total of 25 studies with 4443 patients were included. Compared with venous grafts, arterial grafts had lower MGF (standardized mean difference [SMD], −0.28; 95% confidence interval [CI,  −0.34; −0.22];  P  < .001). OPCABG was associated with significantly lower MGF compared to ONCABG (SMD, −0.29; 95%CI,  −0.50; −0.08];  P  = .01). No differences were found in MGF between skeletonized vs pedicled IMA after anastomosis (SMD, 0.32; 95%CI [−0.08; 0.71];  P  = .11) or in free flow (SMD, 0.76; 95%CI [−0.14; 1.65];  P  = .10). No difference was found in PI between OPCABG and ONCABG. At meta‐regression, age was associated with higher MGF, while OPCABG was associated with lower MGF. Conclusions: Intraoperative flow of venous conduits is higher than that of arterial grafts. Compared to OPCABG surgery, graft flow is higher in ONCABG. In skeletonized and pedicled IMA conduits, no difference in flow profiles was found.